2021
DOI: 10.3390/app11146666
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Low-Cost Multi-Frequency GNSS Receivers and Antennas for Displacement Detection

Abstract: Low-cost Global Navigation Satellite System (GNSS) receivers are currently used in various engineering applications. These low-cost devices are regarded as suitable sensors for applications in areas with a high risk of instrument damage. The main objectives of this research were to identify the size of displacements that can be detected in relative and absolute positioning modes by low-cost GNSS instruments and to compare the results of selected antennas. Additionally, geodetic and low-cost GNSS instruments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Geodetic GNSS devices have advantages over classical geodetic sensors when used in geodetic monitoring, as they can provide high-quality positioning solutions continuously in all weather conditions and with less effort. However, the use of geodetic GNSS devices in monitoring natural hazards such as landslides is not an optimal solution since those devices come with high costs; additionally, the possibility of instrument damage in such unstable areas is high [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geodetic GNSS devices have advantages over classical geodetic sensors when used in geodetic monitoring, as they can provide high-quality positioning solutions continuously in all weather conditions and with less effort. However, the use of geodetic GNSS devices in monitoring natural hazards such as landslides is not an optimal solution since those devices come with high costs; additionally, the possibility of instrument damage in such unstable areas is high [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the obtained results, it was found that horizontal and spatial displacements of 4 and 6 mm can be detected in static relative positioning even through using low-cost GNSS antennas. The magnitude of the detected spatial displacements increased to 20 mm in PPP [7]. In the case of [5], u-blox patch antennas were considered while a geodetic GNSS instrument was used as a reference station.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the performance of small, lightweight, and low-cost GNSS antennas has rarely been evaluated. Hamza et al (2021) 13 and Krietemeyer et al (2020) 14 evaluated the accuracy of GNSS observations and the positioning accuracy of low-cost dual-frequency GNSS receivers, survey GNSS antennas, and small patch antennas. Hamza et al 15 , Poluzzi et al (2020) 16 compared the RTK-GNSS accuracies of three low-cost antennas.…”
Section: Related Studiesmentioning
confidence: 99%
“…Recently, with the introduction of low-cost, dual-frequency, multi-constellation receivers, the RTK technique is becoming more and more popular and used in various applications such as precision agriculture, intelligent transportation, construction machine control, ground mapping, port automation, structure monitoring [3][4][5][6][7].…”
Section: Introduction Rtk (Real-time Kinematicmentioning
confidence: 99%